Expression of Ciona intestinalis AOX causes male reproductive defects in Drosophila melanogaster - Saari, Sina; Andjelkovic, Ana; Garcia, Geovana S. [UNESP]; Jacobs, Howard T.; Oliveira, Marcos T. [UNESP] (Biomed Central Ltd, 2017)
Background: Mitochondrial alternative respiratory-chain enzymes are phylogenetically widespread, and buffer stresses affecting oxidative phosphorylation in species that possess them. However, they have been lost in the evolutionary lineages leading to vertebrates and arthropods, raising the question as to what survival or reproductive disadvantages they confer. Recent interest in using them in therapy lends a biomedical dimension to this question. Methods: Here, we examined the impact of the expression of Ciona intestinalis alternative oxidase, AOX, on the reproductive success of Drosophila melanogaster males. Sperm-competition assays were performed between flies carrying three copies of a ubiquitously expressed AOX construct, driven by the a-tubulin promoter, and wild-type males of the same genetic background. Results: In sperm-competition assays, AOX conferred a substantial disadvantage, associated with decreased production of mature sperm. Sperm differentiation appeared to proceed until the last stages, but was spatially deranged, with spermatozoids retained in the testis instead of being released to the seminal vesicle. High AOX expression was detected in the outermost cell-layer of the testis sheath, which we hypothesize may disrupt a signal required for sperm maturation. Conclusions: AOX expression in Drosophila thus has effects that are deleterious to male reproductive function. Our results imply that AOX therapy must be developed with caution.
Keywords: Mitochondria; Respiratory chain; Spermatogenesis; Sperm competition